2019
DOI: 10.1021/acsinfecdis.8b00373
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus NS5 Forms Supramolecular Nuclear Bodies That Sequester Importin-α and Modulate the Host Immune and Pro-Inflammatory Response in Neuronal Cells

Abstract: The Zika virus (ZIKV) epidemic in the Americas was alarming because of its link with microcephaly in neonates and Guillain-Barrésyndrome in adults. The unusual pathologies induced by ZIKV infection and the knowledge that the flaviviral nonstructural protein 5 (NS5), the most conserved protein in the flavivirus proteome, can modulate the host immune response during ZIKV infection prompted us to investigate the subcellular localization of NS5 during ZIKV infection and explore its functional significance. A mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(86 citation statements)
references
References 96 publications
16
65
0
Order By: Relevance
“…The so‐called α/β NLS (nuclear localization signal) region, including residues around 369–389 , as well as the C‐terminal stretch around amino acids 883–900 , are described to be important for nuclear‐targeting ability and importin‐α/β‐binding activity in the various flaviviruses. Our recent studies of ZIKV NS5 and previous work done by Grant et al . revealed that the protein forms supramolecular nuclear spherical bodies with importin‐α and describes the possible importance of ZIKV NS5's nuclear localization toward neuronal cell‐specific activation of innate immune and proinflammatory pathways.…”
supporting
confidence: 58%
See 3 more Smart Citations
“…The so‐called α/β NLS (nuclear localization signal) region, including residues around 369–389 , as well as the C‐terminal stretch around amino acids 883–900 , are described to be important for nuclear‐targeting ability and importin‐α/β‐binding activity in the various flaviviruses. Our recent studies of ZIKV NS5 and previous work done by Grant et al . revealed that the protein forms supramolecular nuclear spherical bodies with importin‐α and describes the possible importance of ZIKV NS5's nuclear localization toward neuronal cell‐specific activation of innate immune and proinflammatory pathways.…”
supporting
confidence: 58%
“…7A), suggesting that the R681 mutations disrupting the dimer-dimer interface do not affect NS5 protein stability in cells. ZIKV NS5 WT has been demonstrated to localize into distinct spherical bodies within the nucleus [8,56], while DENV-2 NS5 exhibited more diffused-nuclear localization [6]. Interrogation of the ZIKV NS5 mutants' subcellular localization by CLSM revealed that the R681A mutant exhibited a mix phenotype of diffused-nuclear localization similar to DENV-2 NS5, and distinct nuclear body formation in the transfected cells ( Fig.…”
Section: Enzymatic Activity Of Zikv Ns5 and Its Mutantsmentioning
confidence: 87%
See 2 more Smart Citations
“…Apart from these functions, flavivirus NS5 has other viral and cellular roles during virus infection, including the modulation of the host immune response. Interestingly, the subcellular localization of NS5 proteins is different amongst the flaviviruses when examined by immunofluorescence assays, as they have been found in the nucleus and/or cytoplasm [15][16][17][18][19][20][21][22][23][24]. In particular, the observation of these flavivirus NS5 proteins in the nucleus suggests that NS5 plays important cellular and virus roles there, despite its major virus enzymatic role in virus RNA replication in the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%